PENGARUH IDIOSYNCRATIC RISK DAN LIKUIDITAS SAHAM TERHADAP RETURN SAHAM - R. Murhadi, Werner (Jurnal Manajemen dan Kewirausahaan, 2013)
This study examined the effect of idiosyncratic risk and liquidity of shares on stock return. It used data of 50 companies on the Indonesia Stock Exchange 2009–2011 period. The independent variable was the idiosyncratic risk and the liquidity of the shares, as well as control variables such as firm size. Using panel data and pooled least square, result show that idiosyncratic risk had a significant negative effect on stock return, liquidity of the shares had significant positive and significant negative effect of firm size. This means that firms with small idiosyncratic risk that small investors will be preferred, so the demand from individuals and institutions simultaneously will push stock prices and provide a higher return.